Effects of Network Approval on Accounts of Commitment Trajectories in Intraracial and Interracial Relationships. Issue 4 (19th May 2017) - Brooks, James E.; Ogolsky, Brian G.
ABSTRACT: The current study used dyadic data to investigate the impact of relationship type and social support on the retrospective accounts of commitment trajectories of romantic relationships. Past research suggests that social support is a positive contributor to relationship stability and commitment, which may be especially true for partners in interracial relationships who face broader societal opposition than intraracial couples. Using multilevel modeling, we investigated the effects of sex, relationship type, and social support on reports of commitment. Results showed differences in trajectories of commitment based on couple type (interracial vs. intraracial) for both men and women. Social support was found to have an especially strong impact for women in interracial relationships compared with women in intraracial relationships, but there was no differential impact among men.